The costing of operating theatre time in a secondary level, state sector hospital: A quantitative observational study - Samuel, John Philip (Department of Anaesthesia and Perioperative Medicine, 2021)
Background: There is no established costing model for operating theatres in South Africa, yet both sectors have existing charges for operating theatre (OT) time: in the state sector, Uniform Patient Fee Schedule (UPFS) rates, and in the private sector, Rands/minute (R/min) rates for OT time. Understanding the cost of providing the separate components of a health service is important for planning and funding purposes. Objective: The primary objective of this study was to develop a costing model that would allow the calculation of the R/min cost of OT time. The secondary objective was to determine the actual costs, in order to establish the comparable costs that would be included in the R/min charges for OTs in the private health sector. Method: The OTs in a secondary level, state sector hospital in Cape Town were used in this quantitative observational study to develop a top-down costing model for OTs in South Africa. The inclusive costing model was developed in a consultative process with professionals, managers and experts from the state and private sector. The model was then populated with utility measurements (water and electricity) for the month of August 2018, staff salaries, excluding surgeons and anaesthetists, and other costs for the 2018/19 financial year. Results: Costs were considered in the categories of full costs, shared costs and capital or annualised costs. Due to uncertainty in costing of OTs, two models - with different annualisation times assigned to the capital costs - were developed to demonstrate the difference. For shared costs, correction factors were determined using either an activity based (work-load) factor, or a more generic estimation of workload using theatre nursing staff as a percentage of total hospital nursing staff. To determine a R/min cost of creating a minute of available theatre time, all the annual costs were divided by minutes that the OTs are explicitly available, each year, to provide patient care. The model was then populated with costs using the appropriate correction factors. The longer annualisation model costed OT time at R31,46 per minute, and the shorter annualisation model at R33,77 per minute. In both the longer and shorter capital annualisation models, nursing was the largest contributor to costs at 36% and 33% respectively, followed by construction costs at 9% and 11%, and then OT equipment at 8% and 11%. Conclusion: An inclusive, top-down costing model for OTs in South Africa was developed. This costing model will support work to develop costing for individual procedures, the appropriate charge for planned and emergency OT time, and to better determine budgeting for OT services. Meaningful critique of the model will improve its fidelity, and likely increase its utility, especially as SA moves towards universal health coverage.